DHEA Optimizing the Performance of the Four-Wheel Patrol Samapta Unit in Preventing Motor Vehicle Theft in the Legal Area of Polrestabes Semarang (Advances in Police Science Research Journal, 2024)
Curanmor is one type of crime that often occurs in the Semarang Polrestabes area, so appropriate and effective prevention efforts are needed. This study aims to identify the factors that influence the performance of the Samapta Unit's four-wheeled patrol and design a strategy for optimizing the performance of the Samapta Unit's four-wheeled patrol in preventing Curanmor crimes. The method used in this study is a qualitative method with a case study approach. Data were obtained from interviews with members of the Samapta Unit and analysis of documents related to four-wheeled patrol activities. The results showed that the factors affecting the performance of the Samapta Unit's four-wheeled patrol included: a lack of personnel, inadequate vehicles, and a lack of personnel training and development. The strategy for optimizing the performance of the Samapta Unit's four-wheeled patrol includes: increasing the number of personnel and adequate vehicles, training and developing personnel, using information technology, and good coordination with related parties. It is hoped that the results of this research can be input for the police, especially the Samapta Unit in improving the performance of four-wheeled patrols in preventing criminal acts of theft at Polrestabes Semarang. In addition, the results of this study can be a reference for other researchers who wish to conduct similar research in the future.
Keywords: curanmor; optimalisasi kinerja; patroli